Kontribusi Inovasi Kurikulum Terhadap Kinerja Guru Sekolah Dasar: Tinjauan Literatur Sistematis - Shafa Nisa Al-Iman; Effy Mulyasari (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Curriculum changes in elementary education require effective innovation management to improve teacher performance. Although previous studies have examined the relationship between curriculum management and teacher performance, their findings remain fragmented and primarily focus on direct effects without providing an integrated understanding of the underlying mechanisms and emerging research trends. This study addresses this gap by synthesizing existing evidence to develop a comprehensive conceptual understanding of how curriculum innovation management contributes to teacher performance. A Systematic Literature Review (SLR) was conducted following the framework proposed by Xiao and Watson, including problem formulation, review protocol development, literature search, study screening, quality assessment, data extraction, data synthesis, and reporting. Literature published between 2015 and 2026 was retrieved from Google Scholar. Following the PRISMA selection process, 30 studies met the inclusion criteria and were analyzed. The findings indicate that curriculum innovation management enhances teacher performance by strengthening pedagogical competence, instructional creativity, adaptability to curriculum reform, and collaborative professional culture. The review further identifies teacher motivation, organizational commitment, and pedagogical competence as key mediating factors, while principal leadership, professional development, educational policy, and school facilities function as moderating factors. The novelty of this review lies in the development of an integrated conceptual synthesis that explains the interaction between direct, mediating, and moderating factors while identifying current research trends and future research directions. These findings provide evidence-based insights for strengthening curriculum innovation management to improve teacher professionalism and the quality of elementary education.